(untitled) (E Global Congress, 2024)
This article explores the potential of using ChatGPT, an advanced AI language model, in the teaching of English for Specific Purposes (ESP). It discusses how ChatGPT can be utilized to enhance ESP learning through personalized instruction, vocabulary acquisition, real-life simulations, grammar support, and cultural context. The article highlights the advantages of incorporating ChatGPT into ESP classrooms, such as targeted professional language practice and immediate feedback. The study emphasizes the dynamic and interactive nature of ChatGPT, making it a valuable tool for students in specialized fields like business, medicine, law, and engineering. While acknowledging some limitations, the article presents ChatGPT as a transformative tool in ESP teaching, offering new opportunities for students to acquire the language skills needed for their professional careers.